2015
DOI: 10.4269/ajtmh.15-0307
|View full text |Cite
|
Sign up to set email alerts
|

Seroconversion to Japanese Encephalitis Virus Among U.S. Infantry Forces in Korea

Abstract: Abstract. Japanese encephalitis virus (JEV) is endemic in the Republic of Korea (ROK), posing a medical threat to more than 29,000 U.S. Forces military personnel currently deployed in the ROK. The objective of this study was to provide data on the risk of JEV exposure among U.S. Forces in the ROK. One thousand U.S. Army Soldiers were randomly selected for the study from the cohort of infantry Soldiers deployed in the ROK for a period of at least 330 days from 2008 to 2011. Pre-and post-deployment serum specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The risk of developing JE in travellers is hard to determine. Asymptomatic infection is detectable but infrequent 25 , 26 . Disease incidence will be even lower—estimated in European travellers at one case per 5.4 million visits to Asia 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The risk of developing JE in travellers is hard to determine. Asymptomatic infection is detectable but infrequent 25 , 26 . Disease incidence will be even lower—estimated in European travellers at one case per 5.4 million visits to Asia 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Forces Korea (Eick-Cost et al, 2015). They found that prevalence was as low as 0.2% of the population studied, and at least one soldier had titers high enough to indicate current or recent infection.…”
Section: Introductionmentioning
confidence: 96%
“…A 2015 study performed in the Republic of Korea tested the serum of 1,000 soldiers that had never previously deployed to determine the prevalence of JEV antibodies among personnel in the U.S. Forces Korea (Eick-Cost et al, 2015). They found that prevalence was as low as 0.2% of the population studied, and at least one soldier had titers high enough to indicate current or recent infection.…”
Section: Introductionmentioning
confidence: 99%
“…A 2015 study performed in the Republic of Korea tested the serum of 1,000 soldiers that had never previously deployed to determine the prevalence of JEV antibodies among personnel in the U.S. Forces Korea ( 17 ). They found that prevalence was as low as 0.2% of the population studied, and at least one soldier had titers high enough to indicate current or recent infection.…”
Section: Introductionmentioning
confidence: 99%